CONCEPTUAL GREEN DEVELOPMENT IN ORGANIC PRODUCT: A CONSUMER BEHAVIOR APPROACH - Lutfiana, Diana; Nur Endah Retno Wuryandari (Dinasti International Journal of Management Science, 2020)
The Indonesian Organic Agriculture Statistics (SPOI) recorded the number of consumer demand for organic products increased 54 percent compared to the previous year. For more detailed, other data shows 18 percent of customers in Southeast Asia are willing to pay more to buy organic products. The purpose of this study is to predict consumer behavior and investigate in purchase intention organic product which became a trend as well as an attractive business opportunity in the future. This research using the shopping at hypermarkets which is located in jakarta. The research objects have attitude, perceived value, and attribute as factors affecting them to buy organic. The result each factor is positive and significant influence towards Intention to Purchase the green product. The Coefficients table in this research showed the value of attribute as the highest score of consumer behavior in purchase the green product Green action can implement a new trend of lifestyle in consumption organic food in Indonesia. Those all need involvement in marketing activities and will become conceptual strategic for green products that examined in this research.